1980
DOI: 10.1073/pnas.77.10.5611
|View full text |Cite|
|
Sign up to set email alerts
|

Theoretical prediction of the vibrational spectra of group IB trimers

Abstract: The molecular structures of the group IB trimers, Cu 3 , Ag 3 , and Au 3 , have been determined by using the semi-empirical diatomics-in-molecules theory. The trimers are found to have C 2v symmetry with bond angles between 65° and 80°. The trimers are bound with respect to dissociation to the asymptotic limit of an atom plus a diatom. The binding energies per atom for Cu 3 , Ag 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Previous work predicted that the structure has C 2v symmetry with a bond angle between 65 and 80 degrees, 31,32 and we found that most of our density functional theory (DFT) calculations agree with that prediction. The accuracy of xc functionals for geometry in terms of mean unsigned error of bond length is shown in Table 3 along with the percentage of Hartree−Fock exchange.…”
Section: 89supporting
confidence: 77%
“…Previous work predicted that the structure has C 2v symmetry with a bond angle between 65 and 80 degrees, 31,32 and we found that most of our density functional theory (DFT) calculations agree with that prediction. The accuracy of xc functionals for geometry in terms of mean unsigned error of bond length is shown in Table 3 along with the percentage of Hartree−Fock exchange.…”
Section: 89supporting
confidence: 77%
“…For the trimer at the B3LYP level, we found two triangles with C 2v geometries due to the presence of a conical intersection for the equilateral triangle, which leads to a Jahn−Teller distortion. 4,51 The isosceles triangular 2 B 2 state (3b) with a vertex ∠ = 75.7°is predicted to be ∼1 kcal/mol lower in energy than the isosceles triangular structure (3a) with a vertex ∠ = 54.8°for the 2 A 1 state at the B3LYP level; the 2 A 1 state has an imaginary frequency of ∼100i cm −1 . We note that calculations at the B3LYP/aD level incorrectly predict a third geometry with a bond angle of 143°for the 2 B 2 state to be the global minimum by a small amount.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…For C% both experimental observation [8] and ab-initio calculation [9] predicted the trigonal-bipyramidal structure as most stable. The square-bipyramidal form of Cu 6 was calculated [10] as most stable. Agn: The triangular configuration of Ag 3 was found to be more stable [5].…”
Section: Mierodustersmentioning
confidence: 99%